Fossil capital at 10 : Andreas Malm on capitalism, energy, and resistance - Wellum, Caleb; Szeman, Imre; Malm, Andreas (Cultural Studies, 2025)
With the publication of Fossil Capital in 2016, Andreas Malm reshaped how scholars understand the relationship between capitalism and fossil fuels. Energy humanities scholars Caleb Wellum and Imre Szeman interviewed Malm in November 2024 about the arguments and impact of Fossil Capital, the development of his thought in several subsequent books, and the shifting landscape of climate politics. At a time when the stakes of climate politics have never been higher, Malm's work is indispensable. This interview provides an opportunity to revisit Fossil Capital in light of the past decade's developments while also exploring the more radical propositions his recent work has put forth. From the role of sabotage in climate activism to the geopolitical entanglements of energy politics, Malm dissects the complex forces obstructing climate action and explores the strategies that might still be able to disrupt them, however powerful they might be. Readers will find in this conversation reflections on Malm's intellectual evolution and a considered engagement with the urgent question that has animated his work: how to bring about the end of fossil capitalism before it brings about the end of all of us.